HENRIK IBSEN AS A PILLAR FOR SOCIAL TRANSFORMATION - Paul, Rama; Sarkhel, Ranjana Das (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this research is to discuss Henrik Ibsen as one of the pillars of the societal transformation we see in today’s society in contrary with the earlier times. Few of his famous dramas like A Doll’s House, Hedda Gabbler, Ghosts. are being discussed in brief to justify the research conclusion. An online library research method has been used for collecting the data which has been further analysed by qualitative method and on the basis of analysis it has been revealed that Henrik Ibsen is a prudent and has addressed modern times societal issues through his various play way back. Descriptive method has been used for study of the topic. His work has changed the thinking and point of view of people with time, especially towards women in the society. Women learned to fight for their right and listen to herself, the position of women in the society has levelled up and Ibsen’s plays have definitely played an important role in bringing these changes.